Development of Interactive Multimedia Based on Problem-Based Learning on Ecosystem Material to Improve the Analytical Skills of Senior High School Students - Suci Siti Lathifah; Rita Retnowati; Suryani Suryani (CV. Dharma Samakta Edukhatulistiwa, 2025)
This research aims to develop interactive multimedia based on Problem Based Learning that can be installed on Android, and test the effectiveness of its use on the ability to analyse students' ecosystem material. This research is a type of Research and Development, this research was conducted at one of the Bogor Regency State High Schools with the research sample, namely IPA 6 class as the experimental class. The novelty of this research lies in the development of interactive multimedia based on Problem-Based Learning (PBL) specifically designed for ecosystem material to improve the analytical skills of senior high school students, which has not been extensively explored in the context of science education. This development research procedure uses the (4D) model consisting of 4 stages, namely Define, Design, Develop, and Disseminate. The field trial implementation used a one group pretest-postest research design. The techniques used were tests (pre-test and post-test), checklist questionnaire sheets, and documentation. The assessment results show that interactive multimedia gets a very feasible category. This is based on the average percentage of assessment from the expert validation team which is 87%. Interactive multimedia based on Problem Based Learning on android is proven to be effective in improving the ability to analyse students, with an N-gain value of 68.02 included in the medium category. This shows that interactive multimedia based on Problem Based Learning can improve students' analytical skills.